Characterization of the minimal replicon of pHM300 and independent copy number control of major and minor chromosomes of Haloferax mediterranei. Issue 1 (17th December 2012) - Liu, Xiaoqing; Miao, Di; Zhang, Fan; Wu, Zhenfang; Liu, Jingfang; Xiang, Hua
Abstract The presence of minichromosomes is very common in haloarchaea, but little is known about the coordination of replication between the major and minor chromosomes. In this study, we analyzed the replication of pHM300, a 321, 908‐bp minichromosome, which encodes versatile metabolism pathways in Haloferax mediterranei. The replication origin of pHM300 was predicted in the 699‐bp intergenic region between the cdc6K and tbp4 gene, and the minimal replicon, consisting of an AT‐rich region flanked by putative origin recognition boxes (ORBs) and the adjacent cdc6K gene, was determined by assaying for its ability to replicate autonomously in Haloarcula hispanica. Southern blot analysis indicated that the ratio of pHM300 to chromosome increased from the early exponential to middle stationary phase. The copy numbers of these minor and major chromosomes were then evaluated by real‐time PCR and showed that both decreased in stationary phase. However, the decrease in the copy number of the major chromosome was a little earlier and much greater than that of pHM300, revealing that the copy number control of the minichromosome pHM300 is independent from that of the major chromosome in H. mediterranei.